2020
DOI: 10.3390/ani10081377
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Dietary Vegetable Lipid Sources on Health Status in Nile Tilapia (Oreochromis niloticus): Haematological Indices, Immune Response Parameters and Plasma Proteome

Abstract: This study aimed to investigate the effects of DLs, including palm oil (PO; an SFAs), linseed oil (LO; n-3 PUFAs) and soybean oil (SBO; n-6 PUFAs) on the health status of Nile tilapia (Oreochromis niloticus) during adulthood. Three experimental diets incorporating PO, LO or SBO were fed to adult Nile tilapia for a period of 90 days, and haematological and innate immune parameters were evaluated. Proteome analysis was also conducted to evaluate the effects of DLs on plasma proteins. The tested DLs had no signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Consumption of a diet enriched with omega-3 ( n − 3) PUFAs, especially EPA and DHA, can promote an anti-inflammatory environment within the fish body and thereby strengthening its resistance to infectious diseases and targeting maximum production [ 41 ]. Additionally, the health importance of n − 3 fatty acids to humans is the anticipation of cardiovascular diseases, enhancement of visual insight, and strengthening of mental wellbeing [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of a diet enriched with omega-3 ( n − 3) PUFAs, especially EPA and DHA, can promote an anti-inflammatory environment within the fish body and thereby strengthening its resistance to infectious diseases and targeting maximum production [ 41 ]. Additionally, the health importance of n − 3 fatty acids to humans is the anticipation of cardiovascular diseases, enhancement of visual insight, and strengthening of mental wellbeing [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing rapid development of aquaculture has been accompanied by more stressful conditions, which have impaired immune response and augmented disease outbreaks among farmed fish [ 56 ]. Concerning these issues that threaten aquaculture industry, the application of natural functional nutrients enriched with omega-3 (n-3) fatty acids not only has significant regulatory effects on inflammatory response in fish [ 57 ], but also offers healthy food choice for consumers with numerous health outcomes [ 58 ]. It has been shown that many microalgae species have a number of health-promoting impacts, particularly in the prevention and treatment of several diseases owing to their composition from natural antioxidant compounds or production of long-chain PUFAs [ 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hematological parameters are useful indicators of the health and nutritional status of fish (Nakharuthai et al, 2020). Table 5 shows the effect of the experimental diets on the blood parameters of the Nile tilapia.…”
Section: Blood Parametersmentioning
confidence: 99%